Site-specific Fertilizer Nitrogen Management in Irrigated Wheat using Chlorophyll Meter (SPAD meter) in the North-western India - Yadvinder-Singh, Ajay-Kumar, Sandeep Sharma*, H.S. Thind, O.P. Choudhary; Monika Vashis, Bijay-Singh, Varinderpal-Singh (Journal of the Indian Society of Soil Science, 2018)
In irrigated wheat as grown in north-western India, fertilizer nitrogen (N) management following blanket recommendations is increasing resulting in stagnant yield levels with low N use efficiency. Site-specific nutrient management strategy to apply N as per need of wheat crop was formulated based on leaf colour measured by chlorophyll meter (Minolta SPAD meter) as a function of soil N supply. The SPAD meterguided protocols for fertilizer N application at crown root initiation (CRI) and maximum tillering (MT) stages, coinciding with first two irrigations, were evaluated through a series of field experiments with seven wheat varieties in Ludhiana and Gurdaspur in north-western India. Threshold leaf greenness levels equivalent to SPAD readings <40, <42.5 and <45 were tested in terms of (i) whether to apply fertilizer or not, and (ii) deciding as to how much fertilizer N needs to be applied as per requirement of the crop. At CRI stage, when the crop was about two-week old, fertilizer N dose could not be guided by SPAD meter because due to application of a basal dose of N at planting variation in the leaf colour was found to be very small. Also, due to small size of leaves at CRI stage it was difficult to use SPAD meter to measure leaf colour. Application of 30 kg N ha-1 at planting, 45 kg N ha-1 at CRI stage and a dose of 30 or 45 kg N ha-1 at MT stage depending upon leaf greenness to be â‰¥ or < SPAD 42.5, respectively produced wheat grain yields at par with blanket recommendation for fertilizer N, but with higher fertilizer N use efficiency.